2004
DOI: 10.1111/j.1365-2982.2004.00538.x
|View full text |Cite
|
Sign up to set email alerts
|

Human enteric neuropathies: morphology and molecular pathology

Abstract: The aim of this study is to review current understanding of the molecular and morphological pathology of the enteric neuropathies affecting motor function of the human gastrointestinal tract and to evaluate the described pathological entities in the literature to assess whether a new nosology may be proposed. The authors used PUBMED and MEDLINE searches to explore the literature pertinent to the molecular events and pathology of gastrointestinal motility disorders including achalasia, gastroparesis, intestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
210
0
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(217 citation statements)
references
References 144 publications
(255 reference statements)
3
210
0
4
Order By: Relevance
“…Due to the clinical picture and the findings of antroduodenojejunal manometry and histopathological analysis, the patient fulfils the criteria for CIPO (12)(13)(14). The sudden onset of this disease in a previously seemingly healthy young woman puzzled us.…”
Section: Discussionmentioning
confidence: 94%
“…Due to the clinical picture and the findings of antroduodenojejunal manometry and histopathological analysis, the patient fulfils the criteria for CIPO (12)(13)(14). The sudden onset of this disease in a previously seemingly healthy young woman puzzled us.…”
Section: Discussionmentioning
confidence: 94%
“…Cells in ENS are organized as two major plexuses, the myenteric and the submucous plexus, and their main function is to control most of the gastrointestinal functions (33) . Among these functions, we can mention the regulation of enteroendocrine and paracrine secretion, absorption of nutrients and fluids, vascular tone, sensorial information and motility (6,11,14) . Several studies have reported degenerative characteristics in the nervous tissue of the gastrointestinal tract caused by diseases that affect the digestive canal or the ENS itself.…”
Section: Introductionmentioning
confidence: 99%
“…The typical finding is a dense plasma cell and lymphocytic infiltrate in and around the ganglia. The identity of the lymphocytic infiltrate (CD3 positive and both CD4 and CD8 positive cells) suggests a T-cell mediated injury to the ganglionic cells, although B-cells have also been reported [37,38]. Myenteric ganglia are invariably involved however submucosal ganglia may also sometimes be involved.…”
Section: Chronic Intestinal Pseudoobstructionmentioning
confidence: 99%
“…Most cases of chronic intestinal pseudoobstruction are due to primary defects in the contractile apparatus (nerves, interstitial cells of Cajal, smooth muscle cells) of the gut or secondary to an infiltrating disease such as amyloidosis or scleroderma [37][38][39]. Paraneoplastic intestinal pseudoobstruction is most often reported in cases with small cell lung cancer and thymoma and is usually associated with the presence of circulating ANNA-1 antibodies [40][41][42][43][44].…”
Section: Paraneoplastic Chronic Intestinal Pseudoobstructionmentioning
confidence: 99%